Construct Adaptation of Body Positive Online Content Exposure among Emerging Adults in Indonesia - Arrazana, Wardah Almunawwarah; Rahadi Asih, Sali (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Exposure to body positive content on social media is increasing, especially with the widespread use of digital platforms among emerging adults. Body Positive Online Content (BPOC) offers an alternative that promotes body acceptance and challenges narrow beauty standards. This study aimed to adapt and validate an Indonesian version of the BPOC measurement tool. A total of 378 participants aged 18–25 completed an online questionnaire. Psychometric analyses, including confirmatory factor analysis (CFA), construct validity testing, and Cronbach’s Alpha, indicated that the BPOC scale demonstrates good validity and reliability. These findings support the use of the adapted BPOC scale to assess exposure to body positive content within the Indonesian cultural context.Paparan terhadap konten positif tentang tubuh di media sosial semakin meningkat, seiring dengan dominasi penggunaan platform digital pada emerging adults. Body Positive Online Content (BPOC) dipandang sebagai bentuk konten alternatif yang mendukung penerimaan tubuh dan resistensi terhadap standar kecantikan sempit. Untuk memastikan kesesuaian pengukuran BPOC di Indonesia, penelitian ini melakukan adaptasi dan pengujian alat ukur dalam versi Bahasa Indonesia. Sebanyak 378 partisipan berusia 18–25 tahun berpartisipasi dengan mengisi kuesioner secara daring. Hasil uji psikometri melalui confirmatory factor analysis (CFA), uji validitas konstruk, dan koefisien Cronbach’s Alpha menunjukkan bahwa skala BPOC memiliki validitas dan reliabilitas yang baik. Temuan ini mendukung bahwa versi terjemahan skala BPOC dapat digunakan untuk mengevaluasi paparan konten positif tubuh dalam konteks budaya Indonesia.